Material World - Rees, Rod; Video Education Australia (Victoria : Video Education Australia, 1997)
This video gives an introduction to chemical reactions.
Copy available in DVD format
Executive producer, David Brown ; script, Rod Rees
Presenter, Siobhan Gleeson
Keywords: Chemical reactions